Effects of Phyllanthus amarus Schum. & Thonn. Extract on Collagenase Induced Osteoarthritic Rats - Waranee Pradit (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Look-Tai-Bai (Phyllanthus amarus Schum. & Thonn.) has been reported to exhibit anti-inflammation and anti-arthritis properties leading to our interest to examine its beneficial effect in osteoarthritis (OA). Thus this study aimed to explore the chondroprotective potential of P. amarus crude extract (PAE) and its major compounds, phyllanthin and hypophyllanthin, in in vitro and in vivo model. For in vitro study, porcine cartilage explant model induced by 25 ng/ml interleukin-1 beta (IL-1ß) was used in this study. After treated with various concentrations of P. amarus extract, phyllanthin and hypophyllanthin, the culture medium and cartilage discs were collected. The medium was measured for the release of sulfate glycosaminoglycans (s-GAGs) and matrix metalloproteinase-2 (MMP-2) activity by DMMB binding assay and zymography, respectively. The explant tissues were analyzed for the remaining of uronic acid content by carbazole assay and stained with safranin-O for investigation of proteoglycan content. Cell viability of this model was evaluated by lactate dehydrogenase (LDH) assay. Chondroprotective potential of PAE and the major components against IL-1ß-induced cartilage explant degradation were revealed by the decreased s-GAGs level and MMP-2 activity in culture medium consistent with an increase in uronic acid and proteoglycan contents in the explants when compared to the IL-1ß treatment. These results agreed with those of diacerein and sesamin which used as positive controls. Also, these substances did not lead to cell death of chondrocytes. For in vivo study, collagenase induced osteoarthritic rats were used as animal model by intra-articular injection of collagenase type II enzyme. After that, various concentrations of PAE and its major compounds were injected into the OA induced rat joint, once a week, for 5 weeks. Then, articular cartilage and synovial fluid of the rats were collected to investigate pathology of articular cartilage by gross and histology grading. Proteoglycan content was also examined by safranin-O staining. Expression analysis of genes involved with OA in articular cartilage were evaluated by quantitative real time PCR. Gelatin zymography was used to study the expression level of MMP-2 enzyme in synovial fluid as well. The results represented that early stage of OA was induced in this study using collagenase type II enzyme. This circumstance was indicated by mild degradation of cartilage affecting the scores of gross and histopathology. Gene expression profiling between normal control group and OA group also accorded with this event. Nevertheless, proteoglycan contents in cartilage matrix was influenced with reduced level comparing with the normal control group. Increase of proteoglycan content was demonstrated after treated with PAE and its major components in a dose dependent manner, with no change in the normal control. Gene expression analysis showed that PAE enhanced some cartilage matrix protein gene expression level including aggrecan (ACAN) and hyaluronan synthase 1 (HAS-1) but not collagen type II alpha 1 (COL2A1). PAE and its major compounds also decreased MMP-2 and aggrecanase-1 (ADAMT-4) expression level. For catabolic cytokine regulated gene, both IL-1ß and TNF-α was not affected by any substances. MMP-2 activity was suppressed by PAE and its major components as well. Regarding to the above results both in vitro and in vivo, these data illustrated the chondroprotective potential of PAE, phyllanthin and hypophyllanthin in early onset of OA. In addition, better chondroprotective activities of PAE than those of the purified components were disclosed in this study. Hence, these substances may augment its application as chondroprotective drug or dietary supplement for OA treatment and protection.